The curcumin derivative WZ35 activates ROS-dependent JNK to suppress hepatocellular carcinoma metastasis. Issue 5 (16th May 2018) - Wang, Lihua; Han, Lijie; Tao, Zheying; Zhu, Zheng; Han, Lei; Yang, Zhenfei; Wang, Hao; Dai, Dandan; Wu, Liang; Yuan, Zhengzhong; Chen, Tongke
Abstract : Tumor metastasis is the leading cause of cancer death; due to the progress made in the elucidation of the mechanism of cancer cell metastasis, there is hope for patients with severe stages of cancer. Abstract : Tumor metastasis is the leading cause of cancer death; due to the progress made in the elucidation of the mechanism of cancer cell metastasis, there is hope for patients with severe stages of cancer. Curcumin, as a novel anti-cancer drug, has been applied in cancer therapy; however, the toxicity of curcumin hinders its application. Herein, we constructed a novel derivative, WZ35, and evaluated its metastatic inhibition properties in vitro and in vivo . CCK-8 assay was performed to evaluate the tumor suppressive activity of WZ35. Cell apoptosis was detected by flow cytometry analysis. Transwell cell migration assay and RTCA were used to detect cell migration in mock and WZ35-treated cells. Western blotting was performed to analyze molecular alteration with different treatments. In this study, we found that curcumin and its derivative WZ35 could dramatically suppress proliferation, invasion, and migration of the hepatocellular HCCLM3, HepG2, and Huh7 cancer cells. Moreover, the cancer cell metastatic markers MMP-2, MMP-9, and N-cadherin were decreased, and E-cadherin was up-regulated. In addition, our data show that WZ35 promotes ROS-dependent JNK activation that is essential for WZ35-caused cell metastasis suppression. Moreover, the NAC and JNK inhibitor SP600125 could dramatically reverse WZ35-caused MMP-2, MMP-9, and N-cadherin reduction and E-cadherin up-regulation. We have also found that WZ35 exhibits powerful anti-metastasis activity of HCCLM3 in vivo . In conclusion, our data indicated that WZ35 could be a candidate for the treatment of metastatic liver cancer patients.